Managing Change When Improving Accessories Assembly Line According to Lean Six Sigma A Feasibility Study at a Cable Distribution Cabinet Manufacture - Kader, Berwa (My University, 2020)
At ABB Kabeldon, the production of a disconnector required an evaluation. To account for a feasibility study that supported evidence-based decision-making. The aim was to discover how to manage affected resources. To explore and explain preventive arguments for the use of Lean Six Sigma. As an approach to foster inevitable gradual positive change within Accessories. What literature regarded as assembly line balancing was used to create a basis for problem solution. To propose suggestions for higher efficiency and more effectivity. Aligned with one-piece-flow production. Theoretical data encompassed management of operations, people, quality and the correlation between them. Empirical data were ethically deducted from interviews with Operators and team leaders in several departments. From surveys completed by team members throughout the organisation. From observations noted throughout the research project. The data was compiled in a knowledge framework. By combining the Six Sigma model known as SDMMAICS (Select, Define, Measure, Map, Analyse, Improve, Control and Sustain) and the change management model ADKAR (Awareness, Desire, Knowledge, Ability and Reinforcement). The assembly line was also analysed in relation to Lean principles. Namely, pull, flow, takt and zero defects. The results showed positive attitude towards Lean Six Sigma from team members. In general, and in particular at Accessories, it was discovered that more forces worked in favour of than against change. Root causes, wastes, benchmarking and the Q6 model were analysed to produce six suggestions for gradual positive change. Which were followed by suggested control mechanisms to ensure sustainable changes. Also, there was a discussion about the feasibility of a pilot project. In terms of technology, finances, legality, operations and time. Critical success factors to implement such a Lean Six Sigma project were established. Concerning commitment, understanding, experience of team members, collaboration, prioritisation, clarity, purpose and organisation. In conclusion, the suggestions were two-sided. On the one hand, they made it feasible to attain a greater level of production for the customer, relative to industry standards. On the other hand, they were enabling evidence-based decision-making, systematically, for future changes within Accessories. Finally, future research was recommended.
Keywords: Gradual positive change; Lean; Six Sigma; SDMMAICS; one-piece-flow production; assembly line balancing; ADKAR; learning